Trusting Infrastructure: The Emergence of Computer Security Incident Response, 1989–2005. - Slayton, Rebecca; Clarke, Brian (Technology & Culture, 2020)
Historians have tended to analyze maintenance as an intrinsically local activity, something very unlike the development of large technological systems. This article challenges this historiographic dichotomy by examining efforts to construct a global infrastructure for maintaining computer security. In the mid-1990s, as the internet rapidly grew, commercialized, and internationalized, a small community of computer security incident responders sought to scale up their system of coordination, which had been based on interpersonal trust, by developing trusted infrastructure that could facilitate the worldwide coordination of incident response work. This entailed developing not only professional standards, but also institutions for embodying and maintaining those standards in working infrastructure. While some elements of this infrastructure became truly global, others remained regionally bounded. We argue that this boundedness resulted not from the intrinsically local nature of maintenance, but from the historical process of infrastructure development, which was shaped by regionally based trust networks, institutions, and needs.